Exploration of Problem-Based Experimental Learning as a Strategy for Strengthening Science Process Skills in the Digestive System Material - Indar Sri Wening; Noor Laila Sahlan (Journal of Academic Biology and Biology Education, 2024)
Purpose of the study: This study aims to analyze the influence of the experimental method with a problem-based learning approach on students' science process skills in the concept of the digestive system, as well as to measure the effectiveness of implementing this learning strategy in improving students' scientific abilities through active, contextual, and inquiry-based learning activities. Methodology: Quasi-experimental method, pretest-posttest control group design, purposive sampling, science process skills essay test, non-participatory observation sheet, normal gain test, Liliefors test, Fisher test, t-test, quantitative statistical analysis, digestive system learning tools, experimental worksheets, question validation instruments, statistical data processing software, and observations by biology subject teachers. Main Findings: The application of the experimental method with a problem-based learning approach showed a significant increase in students' science process skills. The experimental group achieved a higher normal gain than the control group. The research data were normally distributed and homogeneous. The results of the hypothesis test showed a significant difference in the final test results between the two groups, confirming the effectiveness of the learning strategy in improving science process skills in the digestive system topic. Novelty/Originality of this study: The novelty of this research lies in the integration of experimental methods with a problem-based learning approach specifically for the digestive system to develop science process skills. This study expands understanding of investigation-based biology learning strategies and provides an innovative learning model that can be used to enhance students' scientific competence in a more structured manner.